Pendampingan Usaha Mikro Kecil Menengah Desa Borobudur Dalam Pemasaran Digital Untuk Meningkatkan Perekonomian - Astuti, Marni; Zabidi , Yasrin; Utomo , Bagus Wahyu; Mauidzoh , Uyuunul; Gunawan; Nurdin , Riani (Journal of Appropriate Technology for Community Services, 2024)
The UKM in Borobudur village are diverse, such as food, snacks, brown sugar, leather, etc. The products produced by these UKM are marketed locally through traditional markets, stalls, and kiosks located around Borobudur village. The problem is that the turnover generated by UKM is relatively small because the target market is still local. This is because the marketing strategy used is classified as classic. Market expansion can be done by implementing digital marketing. The increasing use of social media currently opens up great opportunities for business people to carry out promotions. Promotions carried out using social media and displaying interesting content are aimed at increasing tourist interest in visiting tourist areas. The results of the service carried out were able to provide an increased understanding of digital marketing implementation, were able to create digital marketing content, and had a website for product sales and promotion of the cultural potential of Borobudur Village.